Czech Technology Platform on Industrial Safety - Bernatik, Ales; Sikorova, Katerna (Communications - Scientific letters of the University of Zilina, 2008)
At the beginning of June 2007 the Faculty of Safety Engineering founded the Czech Technology Platform on Industrial Safety o.s. (CZ-TPIS). The 1st meeting of the General Assembly launched the activity of this national platform in accordance with the already operating European Technology Platform on Industrial Safety (ETPIS).